Equilibrium Exchange Rates in Oil-Exporting Countries - Korhonen, Iikka; Juurikkala, Tuuli (2012)
We assess the determinants of equilibrium real exchange rates in a sample of oil-dependent countries. Our data cover OPEC countries from 1975 to 2005. Utilising pooled mean group and mean group estimators, we find that the price of oil has a clear, statistically significant effect on real exchange rates in our group of oil-producing countries. Higher oil price lead to appreciation of the real exchange rate. Elasticity of the real exchange rate with respect to the oil price is typically between 0.4 and 0.5, but may be even larger depending on the specification. Real per capita GDP, on the other hand, does not appear to have a clear effect on real exchange rate. This latter result contrasts starkly with many earlier papers on real exchange rate determination, emphasising the unique position of oil-dependent countries.